2003
DOI: 10.1038/emm.2003.35
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces ultraviolet-B induced cell damages and polyamine levels in human skin fibroblasts in culture

Abstract: Abbreviations: GAPDH, glyceraldehyde-3-phosphate dehydrogenase; ODC, ornithine decarboxylase A bstract UV radiation is known to cause photoaging of the skin and is considered one of the leading cause of developing skin carcinogenesis. Melatonin w hich has a highly lipophilic m olecular structure facilitating penetration of cell m em branes and serving as an extra-and intracellular free radical scavenger has been dem onstrated to protect photodam age of skin affected by UV exposure. In this study, w e have exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 23 publications
1
43
0
3
Order By: Relevance
“…It was also noted that for UV-exposed fibroblasts, only 56% of the cells survived upon UV exposure (140 mJ/cm 2 ), while cells pre-incubated with 10−9 M melatonin caused a cell survival rate of 92.5% which was paralleled by significant reduction of lipid peroxidation and cell death [146]. In addition, comparative experiments using UV-treated fibroblasts showed a similar correlation in cell viability in presence of 10−7 M melatonin [147]. Finally, the most recent study suggested that melatonin at 10−3 M can protect NIH3T3 fibroblasts against UVA irradiation (15 J/cm 2 ) [148].…”
Section: Melatonin As a “Guardian” Of The Genome And Cellular And mentioning
confidence: 94%
“…It was also noted that for UV-exposed fibroblasts, only 56% of the cells survived upon UV exposure (140 mJ/cm 2 ), while cells pre-incubated with 10−9 M melatonin caused a cell survival rate of 92.5% which was paralleled by significant reduction of lipid peroxidation and cell death [146]. In addition, comparative experiments using UV-treated fibroblasts showed a similar correlation in cell viability in presence of 10−7 M melatonin [147]. Finally, the most recent study suggested that melatonin at 10−3 M can protect NIH3T3 fibroblasts against UVA irradiation (15 J/cm 2 ) [148].…”
Section: Melatonin As a “Guardian” Of The Genome And Cellular And mentioning
confidence: 94%
“…These observation have strong experimental support from in vitro studies. Thus, melatonin increases cell viability in UV-irradiated fibroblasts by counteracting the formation of polyamine levels ( 68 ), and the accumulation of malondialdehyde while decreasing apoptosis cells ( 69 ). Melatonin has also been shown to protect against UV light-induced damage in human leukocytes.…”
Section: Melatonin As Protector Against Skin Damagementioning
confidence: 99%
“…As previously described (Lee et al, 2003), UVB was supplied by a closely spaced array of seven Westinghouse FS-40 sunlamps, which delivered uniform irradiation at a distance of 38 cm. The energy output of UVB (290-320 nm) at 38 cm was measured with a UVB photometer (IL1350 photometer, International Light, Newburyport, MA).…”
Section: Uvb Irradiationmentioning
confidence: 99%